3D scaffold fabricated with composite material for cell culture and its derived platform for safety evaluation of drugs. (30th January 2022) - Zhang, Yanni; Liu, Le; Li, Na; Wang, Yihua; Yue, Xuanfeng
Abstract: In order to overcome the weakness of conventional approaches for cell culture, and provide cells with more in vivo -like microenvironment for studying hepatotoxicity of drugs, "multiple-in-one" strategy was adopted to fabricate a 3D scaffold of silk fibroin/hydroxyapatite/poly lacticco-glycolic acid (SF/HA/PLGA), where HepG2 cells were cultivated and the toxicity of drugs to the cells was investigated. The prepared 3D scaffold proves to bear proper porosity, excellent mechanical property, steady pH environment and good biocompatibility for cell culture. Furthermore, the validity of the developed 3D-SF/HA/PLGA-scaffold based platform was verified by probing the toxicity of a known drug-induced liver injury (DILI) concern acetaminophen (APAP) to HepG2 cells. Eventually, an application of the platform to dioscin (a medicinal plant extract) reveals the hepatotoxicity of dioscin, which involves the inhibition of the expression of CYP3A4 mRNA in the cells. The developed 3D-SF/HA/PLGA-scaffold platform may become a universal avenue for safety evaluation of drugs.